Pembasmi Obligat Hama Tikus Dari Ampas Teh Terhadap Pertumbuhan Dan Tingkat Mortalitas Rattus norvegicus - Hadita Amila; Nurul Afifah; Ramaidhani Ramaidhani; Fitriani Fitriani (Elkawnie: Journal of Islamic Science and Technology, 2019)
Rat as one of the important pests that attackcrops in Indonesia. This pest attacks food crops in all phases of growth so that it can cause a considerable decrease in crop yields. So it is necessary to eradicate rat pests by using politicians from tea pulp. The purpose of this study was to determine how the influence of political use on rat growth and mortality. The design used is RAL which consists of 5 treatments, namely 0 ml/L, 3 ml/L, 6 ml/L, 9 ml/L, and 12 ml/L. The parameters observed were: mortality, weight, and appetite for mice. Data analysis using ANOVA at 5% significance level and continued with DMRT. The results showed that there was an influence of obligat rat pest use on body weight, appetite, and mortality of mice, obligat rat pest who effectively increased mortality reduced rat body weight, rat appetite and rat mortality in the treatment of 12 ml/L.